Perbedaan Harga Pada Jual Beli Obat - Minta Ito Siregar; Adi Syahputra Sirait (Jurnal El-Thawalib, 2021)
In human live buting and selling is a necessity that can not be abandonet so thet humans cannot live without buying and selling activities. Buying and selling is also a means of helping fellow human beings so thet Islam determines its permissibility. In line with the times, the problem of buying and selling occurs in the wider comunity. One of them is about the price difference in buying ang selling drugs at pharmacies. The problem in this study is how the proce difference in buying ang selling drugs at pharmacies in pasar ujung batu village is and how fiqh muamalah reviews the price differences in buying and selling drugs at parmacies in pasar ujung batu village. This research is a field research. Research conducted by collecting data on phenomena thet occur, natural and natural. The data sources of this research are primary and secondary data. Data collection techniques used field studies, namely observation, inter views, and documen tation. The results of this study indicate that the difference in prices in buying and selling drugs at pharmacies contains elements of injustice and praud in providing prices, namely by differentiating the price of drugs that carry prescriptions prom doctors and those who do not carry prescriptions. Based on the view of muamalah fiqh, it is not allowed to take excessive profits in buying and selling. Therefore, the difference in prices in buying and selling drugs at pharmacies in pasar ujung batu village is not allowed because it contains elements of tyrany and fraud.